Social Media Analytics - Factors affecting business and IT alignment of Social Media Analytics in organizations - Daniels,Fredrik; Friborg,Johan (2016)
Social Media Analytic (SMA) is an emerging trend driven by practitioners to access and ana-lyze the increased volumes of user-generated content. The utilization of SMA provides organ-izations with the potential to improve customer insights, digital presence and foster customer relationships. However, despite the positive aspects, acquisition of an emerging technology presents both technical and operational challenges when it comes to the business and IT alignment. The purpose of this study was to investigate the factors affecting the business and IT alignment of SMA in the organization. We derived our investigated factors from Luft-man’s Strategic Alignment Maturity Model, which we applied and verified empirically. We collected our data by interviewing six coordinators or managers of social media from five pri-vate and public organizations with the ambition to investigate the user perspective on business and IT alignment of SMA. The findings show a distant relationship between business and IT due to the inability to integrate the SMA tool within the investigated organizations. This de-rives from the legal and security aspects which we identify as additional and predominant factors when aligning SMA tools with IT and business infrastructure. Thereby, IT and busi-ness managers should acknowledge these challenges when adopting SMA into their organiza-tions.
Keywords: Business and IT Alignment; Strategic Alignment Model; Strategic Alignment Maturity Model; Social Media Analytics